Photogrammetry in Marine Investigations of Hydrotechnical Projects. Chapter IV. 'Stereophotography of Ice' - Nikoforov,D. I. (1971)
Stereophotography of ice is analyzed so as to present the significance of photographic records in determining the type of ice, its mass and displacement in areas where hydrotechnical structures are to be built. (Author) Trans. of mono. Fotogrammetriya v Morskikh Issledovaniyakh pod Gidrotekhnicheskie Sooruzheniya, Leningrad, 1957 p73-78, by M. Slessers.